2020
DOI: 10.1186/s13104-020-05114-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of commercial veterinary probiotics containing enterococci for transferrable vancomycin resistance genes

Abstract: Objective: Vancomycin resistant enterococci (VRE) are of significant public health concern. The identification of VRE in livestock and food has increased. The objective of this study was to determine if the transferrable vancomycin resistance genes vanA and vanB were present in probiotics marketed for use in animals that claimed to contain Enterococcus spp. Results: Of the 40 products selected, Enterococcus spp. DNA was successfully extracted from 36 products. Of these 36 products with enterococcal DNA, 2 (6%)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In our previous work based on metagenomics, and in agreement with the results of other research groups [7][8][9][10][11], we found that non-fermented [12] and fermented [13] foods or probiotic dietary supplements [14] contain a considerable number of ARGs, some of which are mobile. When bacteria with mobile ARGs are consumed through these foods, the ARGs can enter the digestive tract, where it is conceivable that they may be transferred to non-pathogenic bacteria and facultative pathogenic bacteria.…”
Section: Introductionsupporting
confidence: 91%
“…In our previous work based on metagenomics, and in agreement with the results of other research groups [7][8][9][10][11], we found that non-fermented [12] and fermented [13] foods or probiotic dietary supplements [14] contain a considerable number of ARGs, some of which are mobile. When bacteria with mobile ARGs are consumed through these foods, the ARGs can enter the digestive tract, where it is conceivable that they may be transferred to non-pathogenic bacteria and facultative pathogenic bacteria.…”
Section: Introductionsupporting
confidence: 91%
“…Recently, however, the possibility of some unfavourable or sometimes even adverse effects of probiotic consumption have also been raised [ 3 ]. Several publications indicate that bacterial strains included in probiotic compounds, powders and capsules may contain antimicrobial resistance genes (ARGs) [ 4 , 5 , 6 , 7 ]. Recognising that ARGs may enter into the human body by food (e.g., probiotic products), studies on the genetic characteristics of microorganisms (including bacteria) used in the food chain have been recommended by European Food Safety Authority (EFSA) in recent years [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most probiotics supplements in horses fail to meet the FAO and WHO (2002) 56 definitions because of quality control issues and a lack of specific research currently existing. Several studies indicated that some probiotics in the market that are used as a supplementation in horses did not contain the amounts specified on the product label and any quantity of some microorganisms 62,66,67 .…”
Section: Probiotics In Non-ruminantmentioning
confidence: 99%
“…Another disadvantage of using probiotics in horses is that many products are based on human studies data that may not apply to horses. Furthermore, several studies have shown that antimicrobial-resistant genes could transfer by probiotics in horses 67 , which needs further investigation. Thus, more studies are required to capitalize on probiotics' potential benefits in equines.…”
Section: Probiotics In Non-ruminantmentioning
confidence: 99%